2007
DOI: 10.1177/1073858407299290
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Cortex and Long-Term Memory Encoding: An Integrative Review of Findings from Neuropsychology and Neuroimaging

Abstract: Recent findings have led to a growing appreciation of the role of the lateral prefrontal cortex (PFC) in episodic long-term memory (LTM). Here, the authors will review results from neuropsychological and neuroimaging studies of humans and present a framework to explain how different regions of the PFC contribute to successful LTM formation. Central to this framework is the idea that different regions within the PFC implement different control processes that augment memory by enhancing or attenuating memory for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
424
4
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 532 publications
(483 citation statements)
references
References 121 publications
49
424
4
6
Order By: Relevance
“…Right prefrontal regions also distinguished correct from incorrect trials during presentation of both the sample, and the test displays. Previous findings have suggested that VLPFC and DLPFC may implement control processes that contribute to the processing of item and relational information, respectively, and have shown that this activation predicts subsequent long-term memory performance (Blumenfeld and Ranganath, 2007). The current work extends these findings to encoding and retrieval of relational information in short-term memory.…”
Section: Discussionsupporting
confidence: 70%
“…Right prefrontal regions also distinguished correct from incorrect trials during presentation of both the sample, and the test displays. Previous findings have suggested that VLPFC and DLPFC may implement control processes that contribute to the processing of item and relational information, respectively, and have shown that this activation predicts subsequent long-term memory performance (Blumenfeld and Ranganath, 2007). The current work extends these findings to encoding and retrieval of relational information in short-term memory.…”
Section: Discussionsupporting
confidence: 70%
“…The PFC directs the integration of new learning into existing representations via its projections to the parieto-temporal regions (Bechtereva et al, 2004;Bledowski, Rahm, & Rowe, 2009;Blumenfeld & Ranganath, 2007;Dietrich, 2004;O'Reilly & Rudy, 2001). These brain regions also coordinate to form associative inferences within reactivated memory networks (Henke, Weber, Kneifel, Wieser, & Buck, 1999;Kuhl, Shah, DuBrow, & Wagner, 2010;Schacter, Alpert, Savage, Raucht, Albert, 1996) from different learning episodes (Zeithamova & Preston, 2010;Zeithamova, Schlichting, & Preston, 2012).…”
Section: Stages Of Memory Processingmentioning
confidence: 99%
“…A current literature questioning the historical consensus of STWM and LTDM system partition (for review, see Blumenfeld and Ranganath, 2007) supports the view that hippocampal and prefrontal regions are commonly involved in short-term maintenance and organization of incoming event traces. Such "short-term episodic buffer," by permitting associations and relations to be made among events, may be critical for both STWM protection against interference and the formation of unified memory representation sustaining LTDM.…”
Section: Hippocampal Retinoid Signaling and Organizational Capabilitiesmentioning
confidence: 99%
“…Prompted by a recent literature questioning the historical partition between LTDM and short-term/working memory (STWM) systems (for review, see Blumenfeld and Ranganath, 2007), we recently showed that the LTDM deficit seen in aged mice was secondary to an STWM impairment at encoding in association with hippocampal (and prefrontal) dysfunction (our unpublished data). We speculated that faster decay of incoming event traces in (hippocampo-prefrontal) short-term episodic buffer may hinder relational encoding of temporally discontiguous events into a unified mnemonic representation sustaining LTDM (Wallenstein et al, 1998;Eichenbaum, 2004;Mingaud et al, 2007).…”
Section: Introductionmentioning
confidence: 99%